State of the art of breeding, milking, and milk processing for the production of curdled milk and Wagashi Gassirè in Benin: Practices favoring the contamination of its dairy products - Komagbe, Gwladys S.; Dossou, Alphonse; Seko Orou, Baké Marie-Thérèse; Sessou, Philippe; Azokpota, Paulin; Youssao, Issaka; Hounhouigan, Joseph; Scippo, Marie-Louise; Clinquart, Antoine; Mahillon, Jacques; Farougou, Souaïbou (Frontiers in Sustainable Food Systems, 2023)
This study aimed to identify the factors favouring the contamination of raw cow's milk, curdled milk, and Wagashi Gassirè cheese during their production and preservation in order to develop strategies to improve their quality. A cross-sectional survey of 401 randomly selected stakeholders encompassing all levels of the dairy production chain in the Nikki and Dassa-Zoumé communes of Benin was conducted. The data obtained were analysed using the SAS software for the calculation of frequencies and the R software for classifying the stakeholders based on the hygiene practices they adopted during the production and conservation of raw cow’s milk, curdled milk, and Wagashi Gassirè. The study identified three types of dairy farmers based on how they medically treated their cattle and implemented hygiene practices, including farmers who (1) relied on themselves or received help from veterinarians trained in animal husbandry and milking to monitor the animals on their farms; (2) relied only on veterinarians; and (3) relied only on themselves. The majority of these dairy farmers felt that hygienic milking practices were very restrictive and difficult to implement. In addition, three groups of Wagashi Gassirè producers were identified: (1) producers trained in good hygiene practices who did not boil or sun dry the cheese; (2) producers lacking the infrastructure to protect from weather exposure who used all parts of Calotropis procera for coloured Wagashi Gassirè production; and (3) producers who did not often filter the milk and boiled the Wagashi Gassirè in bags before immersion in simple water or whey. The sanitary quality of milk and milk products is influenced by the diverse handling practices employed by producers. These practices must be considered according to the types of farmers and processors when suggesting improved intervention policies.